Pobiram orumenele liste - Šiftar, Ivan Vanek (University of Maribor Press, 2022)
"I’m picking up yellowed leaves" (2022) is a selection of Šiftar’s poems, which have been in the making for sixty years. The author’s intimate and landscape aesthetic motives, sensitivity to the socially disadvantaged, resistance to the occupier during the war and self-critical thought about the legal profession, whose words justice and truth often escape from definiteness, as well as from any social practice. And as the restless spiritual seeker escapes when he wants to take his "split half" into a harmonious self on the road where "everyone is in a hurry".